2022
DOI: 10.1007/s42978-022-00163-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Intensity Intermittent Hypoxic Training on 3-on-3 Female Basketball Player’s Performance

Abstract: Purpose To investigate the effects of 4 weeks high-intensity interval training in hypoxia on aerobic and anaerobic performance of 3-on-3 basketball players. Methods In a randomised controlled trial, 15 female basketballers completed eight 1-h high-intensity training sessions in either normobaric hypoxia (hypoxic group n = 8, altitude 3052 m) or normoxia (normoxic group n = 7, sea-level). Results After training, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…When the athletes returned to sea level, an increased efficiency of displacements was found, with a reduction in total distance and at low intensity, speed changes, and jumps, as well as maintaining or increasing the high-intensity distance. This efficiency and higher performance are in agreement with other basketball research reporting improved highintensity running capacity [13] and on-court agility performance [12,14] following hypoxic training. In addition, the increased aerobic demands under hypoxia concur with past studies documenting superior VO2 MAX development [11] and faster heart rate recovery [34] in basketball players after altitude training.…”
Section: Effects Of Altitude On Internal and External Workloadsupporting
confidence: 91%
See 2 more Smart Citations
“…When the athletes returned to sea level, an increased efficiency of displacements was found, with a reduction in total distance and at low intensity, speed changes, and jumps, as well as maintaining or increasing the high-intensity distance. This efficiency and higher performance are in agreement with other basketball research reporting improved highintensity running capacity [13] and on-court agility performance [12,14] following hypoxic training. In addition, the increased aerobic demands under hypoxia concur with past studies documenting superior VO2 MAX development [11] and faster heart rate recovery [34] in basketball players after altitude training.…”
Section: Effects Of Altitude On Internal and External Workloadsupporting
confidence: 91%
“…A few studies in basketball have shown the improvement of aerobic capacities [12], high-intensity running performance [13], and on-court high-intensity actions (sprints, jumps, change in direction, etc.) following hypoxic training [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The score is obtained from the distance travelled during the test treatment, after which it is calculated using the Yo-yo Intermittent Recovery Test formula. Yo-yo Intermittent Recovery Test level 1 takes around 6-20 minutes per session (Smith et al, 2022); (Ramirez-Campillo et al, 2018). Data analysis techniques include descriptive analysis, prerequisite tests (normality and homogeneity tests), and hypothesis testing using paired sample tests and independent sample tests.…”
Section: Methodsmentioning
confidence: 99%
“…In last decade, a growing number of "Live Low-Train High" altitude training methods have emerged that include the application of systemic and local hypoxia stimuli, or a combination of both, for performance enhancement [5]. One such method is high-intensity interval training in hypoxia, which was investigated by Smith et al [11] in female 3 × 3 basketball players. Authors observed that the addition of hypoxia to four weeks of high-intensity training improved maximal aerobic performance, shuttle run performance and muscular power compared to a normoxic condition.…”
Section: Olivier Girardmentioning
confidence: 99%